Pengembangan Sistem Informasi Pemetaan Perilaku Pelanggan dengan Prediktor Length, Recency, Frequency dan Monetary (Studi pada Bagian Marketing Radio Kalimaya Bhaskara) - Faisal Kamal; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Radio Kalimaya Bhaskara require a system that can segmentation their customer to identify potention and characteristic of each customer using LRFM (Length, Recency, Frequency, Monetary) method. Development of customer relatioship management system using system development life cycle v-model to implement 13 functional requirements and 1 non-functional requirementresulting from elicitation process. Result of software design including sequence diagram, class diagram, design of database, design of interface, and calculation of LRFM value from transaction data. Implementation of software design using programming language PHP and MySQL as database management system. Testing technique on system including unit testing , integration testing, system testing, acceptance testing and security testing.Unit testing perform to 2 function unit and give an output that those function unit are easy to understand, easy to test and can easily to implement. Integration testing perform to 2 function unit and give a result that match with expected result, so it can be said valid. System testing perform to 13 functional requirements and the result match with expected result, so it can be said valid. Acceptance testing explain that stakeholder have approved all functions that have been provide on system. Security testing perform SQL Injection testing to login from and succeed. The comparison results of manually LRFM calculation and through the system give the same customer segmentation results.